2003
DOI: 10.1152/ajprenal.00407.2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of testosterone on regulation of ODC, antizyme, andN1-SSAT gene expression in mouse kidney

Abstract: Polyamines are involved in the control of the cell cycle and cell growth. In murine kidney, testosterone enhances gene expression of ornithine decarboxylase (ODC), the first enzyme in polyamine biosynthesis. In this study, we document the time course effect of testosterone on 1) gene expression of ODC, antizyme 1 (AZ1), and spermidine/spermine-N1-acetyltransferase (N1-SSAT); 2) ODC activity in proximal convoluted tubules (PCT) and cortical proximal straight tubules (CPST); and 3) renal polyamine levels. Female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Translational regulation of AdoMetDC by polyamines, in particular the activating effects of putrescine, has been the subject of intensive investigation [27][28][29]. Our results have demonstrated that polyamine regulation of AdoMetDC activity also occurs in vivo, a finding in line with those reported by other groups [30,31]. Consistent with this notion, in our experimental model of kidney hyperplasia, we found that the activity of AdoMetDC correlated positively with renal putrescine content and negatively with spermine content.…”
Section: Regulation Of the Expression Of Enzymes Involved In Polyaminsupporting
confidence: 91%
See 1 more Smart Citation
“…Translational regulation of AdoMetDC by polyamines, in particular the activating effects of putrescine, has been the subject of intensive investigation [27][28][29]. Our results have demonstrated that polyamine regulation of AdoMetDC activity also occurs in vivo, a finding in line with those reported by other groups [30,31]. Consistent with this notion, in our experimental model of kidney hyperplasia, we found that the activity of AdoMetDC correlated positively with renal putrescine content and negatively with spermine content.…”
Section: Regulation Of the Expression Of Enzymes Involved In Polyaminsupporting
confidence: 91%
“…We have documented that both mRNA content and the activity of SSAT were significantly increased by antifolate CB 3717 (Table 1) and folate injury [15]. In contrast, despite an increase in SSAT mRNA synthesis, a finding consistent with reports from other groups [30,31], SSAT activity was downregulated in the testosterone-induced hypertrophic kidney. Testosterone-induced reduction in SSAT activity (over 40%) was completely abolished by the anti-androgen casodex, implying a role for androgen receptors in the regulation of SSAT [15].…”
Section: Regulation Of the Expression Of Enzymes Involved In Polyaminsupporting
confidence: 85%
“…This gene was shown to be unaffected by estradiol in mammalian systems by Green et al (1998). Furthermore, Levillain et al (2003) recently showed that SSAT is inducible by testosterone in the male mouse kidney. Further study is needed to explore the potential of SSAT as an androgenic biomarker.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in the kidneys of both male and female mice, ODC gene is very sensitive to androgens and is positively regulated by pharmacological and physiological levels of testosterone [39]. Injections of testosterone to mice induce: (1) an upregulation of ODC gene in the three segments of the proximal tubule (PCT, CPST and OSPST) [28], (2) a sharp enhancement in the plasma, renal and urinary level of putrescine [28], and (3) an overexpression of AII gene (manuscript submitted). Interestingly, in the kidneys of testosterone-treated female mice, OAT activity is lower than that of the controls.…”
Section: Discussionmentioning
confidence: 99%